The Cold Avoidance of Typhoons in Their North Turning Over the South China Sea - Lai, Shaojun; Li, Ying; He, Fen; Wang, Yufei; Chen, Yan (Frontiers in Earth Science, 2021)
Based on the typhoon best tracks of China Meteorological Administration (CMA), ERA5 reanalysis data of ECMWF at 0.25 degrees horizontal resolution and NOAA optimal interpolated sea surface temperature (OISST V2) data, the dynamical compositing analysis is used to study the north turning at nearly 90 degrees of four westward typhoons over the South China Sea (SCS). The composite analysis results show that: 1) As the typhoon going westward into the SCS, the upper-level westerly trough moves eastward to the vicinity of 110°E in the mainland of China and the western North Pacific subtropical high (SH) retreats eastward at the same time, which weakens the steering flow of typhoon and slowed down its movement. 2) The cold air guided by the westerly trough invades southwardly into the western part of SCS from the mainland leading to a descending and divergent airflow in the lower-to-middle atmospheric layers and enhancing the eastward pressure gradient force (PGF) in the typhoon’s west quadrant, which block and repel the typhoon moving westward further. 3) Due to the cold air intrusion, the vertical atmospheric stratification in the west quadrant of typhoon becomes static stable, which may suppress the convection, impeding a typhoon westward motion. 4) With the cold air involving to the south of typhoon, the direction of the PGF on the typhoon switches from the eastward to the northward, and the SH falling southward enhances the southwesterly airflow on the south of the typhoon at the same time. The remarkable increasement of northward steering airflows of typhoon results in a northward turning abruptly. 5) In addition, the sea surface temperature (SST) and the ocean heat content (OHC) on the western part of the SCS is also reduced obviously attributed to the cold air cooling, and the typhoon is likely to avoid the cold ocean and approach a relative warming region. This study suggests that a cold avoidance during the westward movement of typhoons is worthy of considering in the operational forecast of typhoon tracks..